Measurement invariance of the SOC-13 sense of coherence scale across gender and age groups - Grevenstein, Dennis; Blümke, Matthias (European journal of psychological assessment, 2022)
. Sense of coherence (SOC) describes an individual’s ability to deal with life challenges (manageability), comprehend the environment (comprehensibility), and perceive life and its challenges as meaningful (meaningfulness). We examine measurement invariance (MI) of the SOC-13 scale across gender and age groups in a matched sample of N = 1,816 (50% females; age range 16-83 years). A two-factor model, with a common factor for manageability/comprehensibility items and a second factor for meaningfulness items, best represented the SOC-13 in all groups. Full metric, partial scalar, and full strict invariance held across gender groups. Across age groups, full metric, partial scalar, and partial strict invariance could be established. We conclude that SOC-13 is a reliable and valid measure. Measurement is comparable across gender and age.
Published online May 26, 2021
Gesehen am 09.09.2022